Benefits, Barriers and Enablers of Breastfeeding: Factor Analysis of Population Perceptions in Western Australia - Daly, Alison; Pollard, Christina; Phillips, M.; Binns, Colin (PLOS, 2014)
Objective: The objective of this study was to investigate knowledge and community perceptions of breastfeeding in Western Australia using a factor analysis approach. Methods: Data were pooled from five Nutrition Monitoring Survey Series which included information on breastfeeding from 4,802 Western Australian adults aged 18–64 years. Tetrachoric factor analysis was conducted for data reduction and significant associations identified using logistic, ordinal and poisson regression analyses. Results: Four factors were derived for benefits (it’s natural, good nutrition, good for the baby, and convenience), barriers (breastfeeding problems, poor community acceptability, having to go back to work, and inconvenience) and for enablers (breastfeeding education, community support, family support and not having to work).As assessed by standardized odds ratios the most important covariates across benefit factors were: importance of breastfeeding (ORs range from 1.22–1.44),female gender (ORs range from 0.80 to 1.46), being able to give a time for how long a baby should be breastfed (ORs range from 0.96 to 1.27) and education (less than high school to university completion) (ORs range from 0.95 to 1.23); the most important covariate across barrier factors was being able to give a time for how long a baby should be breastfed (ORs range from 0.89 to 1.93); and the most important covariates across all enabling factors were education (ORs range from 1.14 to1.32) and being able to give a time for how long a baby should be breastfed (ORs range from 1.17 to 1.42).Conclusions: Being female, rating breastfeeding as important, believing that babies should be breastfed for a period of time and education accounted for most of the statistically significant associations. The differences between male and female perceptions require investigation particularly in relation to returning to work.